Hubungan Pengajaran Firman Tuhan Pembina Terhadap Pemahaman Alkitab Anak Youth di Gereja Bethel Tabernakel Alfa Omega Sampit Kalimantan Tengah Tahun 2022-2023 - Zai, Serika; Rombe, Eni; Susilo, David Priyo (Syntax Corporation, 2025)
The teachings of Jesus serve as an example for the church to nurture and prepare for the future of the Church as heirs of the Kingdom of God (James 2:5). However, in reality, many parents, elders, and church members neglect the educational patterns and faith-building processes for children and youth. This study aims to assess the level of teaching of the Word of God for the TYF